Analisis Bahasa Sarkasme Pada Komentar Netizen Terhadap Pemberitaan Rohingya Di Akun Tiktok Tribun Bogor - Siti Tohira; Indrawati; Ahmad Harun Yahya (CV. ITTC INDONESIA, 2024)
In an era of ever-growing technological advances, social media has become an increasingly important communication platform for society. With the ability to send messages that only require text on the cellphone screen, these messages can be spread quickly to various places according to the wishes of the sender. A study conducted by researchers aimed to explore the analysis of sarcasm in netizen comments on Rohingya news on the Tribun Bogor TikTok account. This research focuses on identifying various forms of sarcasm used in netizen comment columns regarding Rohingya news on these accounts, with in-depth content analysis. Researchers also conducted qualitative analysis of these comments to identify groups of forms of sarcasm that emerged. The results of this research reveal the significant use of sarcastic language in netizen comments regarding Rohingya news on the TikTok account @Tribunbogor. Through focused analysis of sarcasm styles such as propositional, lexical, 'like'-prefixed, and illocutionary sarcasm, researchers succeeded in identifying significant levels of sarcastic language use. From the 23 comment samples analyzed, significant variations in the use of sarcastic style were clearly visible. The two video posts that were the focus of the research, namely